Sexual Function Is an Indicator of Central Arterial Stiffness and Arterial Stiffness Gradient in Japanese Adult Men - Hiroshi Kumagai (Wiley, 2018)
BackgroundAs arterial stiffness increases in the absence of subjective symptoms, a personal indicator that reflects increased risk of cardiovascular disease is necessary. Penile erection is regulated by vascular function, and atherosclerosis affects the penile artery earlier than it affects the coronary and carotid arteries. Therefore, we hypothesized that deterioration of erectile function could be a marker of increased risk for cardiovascular disease. To test our hypothesis, we assessed erectile function and arterial stiffness in a cross‐sectional study. Methods and ResultsCarotid‐femoral pulse wave velocity (PWV), brachial‐ankle PWV, femoral‐ankle PWV, and arterial stiffness gradient (PWV ratio: carotid‐femoral PWV/femoral‐ankle PWV) were measured as indexes of central, systemic, and peripheral arterial stiffness and peripheral organ damage, respectively, in 317 adult men. In addition, erectile function was assessed by using the questionnaire International Index of Erectile Function 5 (a descending score indicates worsening of erectile function). The scores of male sexual function were inversely correlated with carotid‐femoral PWV (rs=−0.41), brachial‐ankle PWV (rs=−0.35), femoral‐ankle PWV (rs=−0.19), and PWV ratio (rs=−0.33). Furthermore, multivariate linear regression analyses revealed that International Index of Erectile Function 5 scores were significantly associated with carotid‐femoral PWV (β=−0.22) and PWV ratio (β=−0.25), but not with brachial‐ankle PWV and femoral‐ankle PWV. ConclusionsOur results indicated that erectile function is independently associated with central arterial stiffness and peripheral organ damage. These findings suggest that male sexual function could be an easily identifiable and independent marker of increased central arterial stiffness and peripheral organ damage.